Особливості інвестування у людський капітал на машинобудівних підприємствах - Бондаренко, В.М.; Кирлик, Н.В. (Економіка промисловості, 2013)
Розглянуто запропоновані вітчизняними та зарубіжними вченими підходи до класифікації інвестицій та їх складові елементи. Виконано аналіз та відображено динаміку двох складових компонентів інвестицій у людський капітал підприємства: навчання новим професіям, підготовка та перепідготовка на виробництві в машинобудівній галузі Закарпатської області та на рівні окремих підприємств регіону. Розраховано та проаналізовано щорічні індекси навчання новим професіям і підвищення кваліфікації працівників на досліджуваних рівнях. Рассмотрены предложенные отечественными и зарубежными учеными подходы к классификации инвестиций и их элементы. Проведен анализ и представлена динамика двух составляющих компонентов инвестиций в человеческий капитал предприятия: обучение новым профессиям, подготовка и переподготовка на производстве в машиностроительной отрасли Закарпатской области и на уровне отдельных предпритий региона. Рассчитаны и проанализированы ежегодные индексы обучения новым профессиям и повышение квалификации работников на исследуемых уровнях. Investing into their employees the industrial enterprises receive guarantees that their activities will be profitable, and production will be served by qualified and productive staff that can innovate and apply them successfully in practice. However, the main problem is the unwillingness of Ukrainian industry owners to invest in training and education of their own staff as they seek to extract maximum profits by investing the minimum amount of financial resources. The main objective of the study was to reveal the theoretical aspects of investing in the human capital of employees and the analysis of the investment process by types at the machine-building enterprises in the Transcarpathian region. For achievement of the main objective the article was structured into stages: clustering of approaches by domestic and foreign scholars as to the classification of investments in the human capital of a company; developing the authors’ structure of costs for asset growth of human capital and the study of their origin; analysis of the level of human capital investment of employees by components at the machine-building enterprises of Transcarpathian region. The authors have formed the following components of the human capital investments: education, innovation and creativity, migration, motivation to work, training and retraining in manufacturing, health care. The analysis of investment in training and retraining of workers shows that the most active investment processes in this area were among the three types of machine-building enterprises, namely the production of electrical, electronic and optical equipment. The enterprises producing vehicles and equipment in 2010-2011 were not investing in such areas as retraining of employees and learning new professions, which was caused, according to the authors, by the transition from the CKEA-2005 to CKEA-2010. The learning of new professions and retraining of staff was the most active until 2009, while the decline of investments has been observing since 2010 due to the crisis situation in Ukraine. Moreover, the lesser was the amount of production sold, the more investments were made by the machine-building enterprises into the training of personnel and their qualification. Over the past 3 years the trend can be traced to a decline in investments in surveyed areas at all enterprises, that might be caused by the global financial crisis, which resulted that the enterprises were forced to cut their spending.